2013
DOI: 10.1002/jrs.4316
|View full text |Cite
|
Sign up to set email alerts
|

Observation of persistent α‐helical content and discrete types of backbone disorder during a molten globule to ordered peptide transition via deep‐UV resonance Raman spectroscopy

Abstract: The molten globule state can aide in the folding of a protein to a functional structure and is loosely defined as an increase in structural disorder with conservation of the ensemble secondary structure content. Simultaneous observation of persistent secondary structure content with increased disorder has remained experimentally problematic. As a consequence, modeling how the molten globule state remains stable and how it facilitates proper folding remains difficult due to a lack of amenable spectroscopic tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…CD spectroscopy has many advantages and is often used for rapid assessment of protein structure. However, studies on smaller nonglobular proteins show that the CD and dUVRR spectra can suggest dramatically different secondary structure distributions . Similar discrepancies were observed between the CD and dUVRR spectra of melittin in DMPC liposomes at 37°C and with 5α‐cholestan‐3β‐ol, where a large loss of helical structure could be inferred from the CD spectra (Figures and ), but the dUVRR spectra indicated that the helical structure of melittin remains largely intact.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…CD spectroscopy has many advantages and is often used for rapid assessment of protein structure. However, studies on smaller nonglobular proteins show that the CD and dUVRR spectra can suggest dramatically different secondary structure distributions . Similar discrepancies were observed between the CD and dUVRR spectra of melittin in DMPC liposomes at 37°C and with 5α‐cholestan‐3β‐ol, where a large loss of helical structure could be inferred from the CD spectra (Figures and ), but the dUVRR spectra indicated that the helical structure of melittin remains largely intact.…”
Section: Discussionmentioning
confidence: 59%
“…The intensity of the amide III band at 1240 cm −1 increases concurrently with a decrease in the negative ellipticity at 222 nm (Figure ). The position and intensity of the lowest frequency amide III band has been shown to be dependent on the ψ dihedral angle . The appearance of a band at 1240 cm −1 is consistent with formation of a small amount of 3 10 ‐helical structure, possibly at the termini of the α‐helix .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Brown and coworkers used deep‐UV resonance Raman spectroscopy to observe persistent α‐helical content and discrete types of backbone disorder during a molten globule to ordered peptide transition. Among other results, their observations indicate that there is a decrease in the structural populations able to explore various extended conformations with successive heme binding events . Di et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, an increase in the amide III intensity at 1240 cm -1 can be observed with increasing temperature in the spectra above 22°C. Given that there is little change in the amide S intensity, this indicates that the helical structure of the melittin remains intact 58 .…”
Section: Resultsmentioning
confidence: 99%